Horizon scanning of potential environmental applications of terrestrial animals, fish, algae and microorganisms produced by genetic modification, including the use of new genomic techniques - Miklau, Marianne; Burn, Sarah-Joe; Eckerstorfer, Michael; Dolezel, Marion; Greiter, Anita; Heissenberger, Andreas; Hörtenhuber, Stefan; Zollitsch, Werner; Hagen, Kristin (Frontiers in Genome Editing, 2024)
With scientific progress and the development of new genomic techniques (NGTs), the spectrum of genetically modified organisms (GMOs) modified for various purposes is rapidly expanding and includes a wide range of taxonomic groups. An improved understanding of which newly developed products may be introduced into the market and released into the environment in the near and more distant future is of particular interest for policy makers, regulatory authorities, and risk assessors. To address this information need, we conducted a horizon scanning (HS) of potential environmental applications in four groups of organisms: terrestrial animals (excluding insects and applications with gene drives), fish, algae and microorganisms. We applied a formal scoping review methodology comprising a structured search of the scientific literature followed by eligibility screening, complemented by a survey of grey literature, and regulatory websites and databases. In all four groups of organisms we identified a broad range of potential applications in stages of basic as well as advanced research, and a limited number of applications which are on, or ready to be placed on, the market. Research on GM animals including fish is focused on farmed animals and primarily targets traits which increase performance, influence reproduction, or convey resistance against diseases. GM algae identified in the HS were all unicellular, with more than half of the articles concerning biofuel production. GM algae applications for use in the environment include biocontrol and bioremediation, which are also the main applications identified for GM microorganisms. From a risk assessor's perspective these potential applications entail a multitude of possible pathways to harm. The current limited level of experience and limited amount of available scientific information could constitute a significant challenge in the near future, for which risk assessors and competent authorities urgently need to prepare.